Dinamika Oikumenika di Kalangan Orang Kristen Pada Masa Kini - Frischa Nofrianti; Meditatio Situmorang (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The ecumenical movement, which aims to unite divided Christian churches, continues to develop with complex dynamics among Christians today. Despite differences in doctrines, traditions and worship practices between denominations, the movement focuses on the unity of faith in Christ through inter-church dialog and social cooperation. Oikumene is a movement that aims to unite divided Christian churches, emphasizing unity in faith in Jesus Christ as Lord and Savior. The history of ecumenism dates back to the Council of Nicea in 325 AD, which aimed to unite the divided churches. This journal will explore the dynamics of ecumenics among Christians today, highlighting the dynamics of ecumenical development, opportunities, challenges, and efforts to be made.